2010
DOI: 10.1186/1471-2164-11-64
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the genomic content of circulating Bordetella pertussis strains isolated from the Netherlands, Sweden, Japan and Australia: adaptive evolution or drift?

Abstract: BackgroundBordetella pertussis is the causative agent of human whooping cough (pertussis) and is particularly severe in infants. Despite worldwide vaccinations, whooping cough remains a public health problem. A significant increase in the incidence of whooping cough has been observed in many countries since the 1990s. Several reasons for the re-emergence of this highly contagious disease have been suggested. A particularly intriguing possibility is based on evidence indicating that pathogen adaptation may play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
62
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 55 publications
(80 reference statements)
8
62
0
7
Order By: Relevance
“…Although no evidence of gene gain has been reported, many previous studies have identified regions of difference resulting from apparent deletions conserved among circulating isolates in comparison with older references (12, 14, 50, 51). The conserved structural features identified here, specifically those which differentiated isolates with the ptxP3 allele and vaccine reference strains, included deletions flanked by IS481 insertions, each of which corresponds to regions of difference identified previously (12,14,25,(50)(51)(52)(53). However, conserved rearrangements and inversions were also identified, illustrating that structural genome evolution in B. pertussis is not limited to reduction.…”
Section: Discussionmentioning
confidence: 53%
“…Although no evidence of gene gain has been reported, many previous studies have identified regions of difference resulting from apparent deletions conserved among circulating isolates in comparison with older references (12, 14, 50, 51). The conserved structural features identified here, specifically those which differentiated isolates with the ptxP3 allele and vaccine reference strains, included deletions flanked by IS481 insertions, each of which corresponds to regions of difference identified previously (12,14,25,(50)(51)(52)(53). However, conserved rearrangements and inversions were also identified, illustrating that structural genome evolution in B. pertussis is not limited to reduction.…”
Section: Discussionmentioning
confidence: 53%
“…The SNP in sphB1 was a common SNP found in all Australian B. pertussis SNP profile 13 (cluster I) isolates from the 2008-2012 epidemic that were sequenced previously while the SNP in fliM was only found in a subset of the isolates [15]. Genomic content of currently circulating B. pertussis strains has been reduced compared to other SNP clusters [38][39][40]. One or more of these changes may provide a selective advantage to the SNP cluster I strains for increased colonisation of the host.…”
Section: Discussionmentioning
confidence: 99%
“…This, combined with very high levels of nucleotide sequence identity in the bpsA-D promoter regions, the similar arrangement of the bpsR ORF with respect to the bpsA-D locus, and the highly homologous amino acid sequences of the BpsR proteins among these three species, suggests the preservation of a common bacterial strategy to regulate virulence and biofilm development. By analyzing the genomic content of a large collection of B. pertussis strains isolated over the last 60 years from six different countries, a core genome for B. pertussis has been derived (4,33). In addition, a group of 589 variable genes that were either absent or divergent in one or more of these strains were also iden-tified (33).…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the genomic content of a large collection of B. pertussis strains isolated over the last 60 years from six different countries, a core genome for B. pertussis has been derived (4,33). In addition, a group of 589 variable genes that were either absent or divergent in one or more of these strains were also iden-tified (33). None of the genes of the bpsA-D locus, the intervening gene, BP1945, or the bpsR gene was found to be missing or divergent in these strains, strongly suggesting that these genes are part of the B. pertussis pan-genome.…”
Section: Discussionmentioning
confidence: 99%